Model Reference Adaptive Control based on a Self-Recurrent Wavelet Neural Network Utilizing Micro Artificial Immune Systems - Omar Farouq Lutfy (Al-Khwarizmi College of Engineering – University of Baghdad, 2017)
Abstract